2018
DOI: 10.1007/s00784-018-2438-6
|View full text |Cite
|
Sign up to set email alerts
|

Marginal adaptation of lithium disilicate ceramic crowns cemented with three different resin cements

Abstract: The resin material that features a three-step protocol (Variolink II) produced higher MG and AMG values than the Panavia or Relyx Unicem varieties with less or no intermediate steps at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
3
7
0
1
Order By: Relevance
“…The involvement of multiple observers allows controlling this error in the statistical model. The whole coefficient of variation in AMD measurement was between 22 and 26% in our study, which was similar to the CV in recent microCT studies [52,[57][58][59]61]. In conclusion, these results highlight the importance of involving multiple observers in the analyses and indicate the high accuracy of the microCT method.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The involvement of multiple observers allows controlling this error in the statistical model. The whole coefficient of variation in AMD measurement was between 22 and 26% in our study, which was similar to the CV in recent microCT studies [52,[57][58][59]61]. In conclusion, these results highlight the importance of involving multiple observers in the analyses and indicate the high accuracy of the microCT method.…”
Section: Discussionsupporting
confidence: 90%
“…The microCT with high resolution increases the contrast of the margin line of the specimens, which could improve the measurement. In this study, an extremely high resolution (8.7 μm) was used, higher than previous studies with 10-19 μm resolution [52,[57][58][59]. The high resolution could contribute to the significant findings in our study despite the low sample number.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The VLE group showed lower mean AMD values compared with a study conducted by Peroz et al that investigated the marginal fit of cemented lithium disilicate ceramic crowns using 3 different luting materials, in which a mean AMD value of 412 μm was measured for the Variolink group. On the other hand, the RelyX Unicem group showed a mean AMD of 213 μm, which is similar to the RX group of the present study [30]. For the NX3 group, no studies could be found to compare the marginal fit values.…”
Section: Discussionsupporting
confidence: 78%